O uso das mídias sociais no poder público: análise do perfil 'Senado Federal' no Facebook - Santos, Gustavo Henrique Campos dos (2016)
Social media such as Facebook can represent to the state a new channel of communication for interaction with citizens, both for dissemination of public information and social control of government acts, and for monitoring the resulting content of this interaction. Through the analysis of materials of social media, public administrators would be able to instrumentalize the public interest for the development of more effective public policies that meets or even exceeds the needs of society. In this sense, the present work aims to analyze the use of social media as a tool of political participation of citizens from the study of the profile "Senado Federal" on Facebook. To fulfill this objective, the post called "And now, who can defend myself?" dated August 2015 was analyzed. The publication deals with the effectiveness of civil rights, being considered one of the most successful profile publications. As a result of the research, we realize the importance of social media for enhancing the state-society interaction. There is a large share of Internet users in the content posted by the Senate in the study profile, due to the use of the channel for the promotion of citizenship. Although the tool is still very little used for monitoring the content produced by Internet users, there is a number of advantages in the use of social media to communicate with the society, including the costs for operation.